2020
DOI: 10.1017/eaa.2020.51
|View full text |Cite
|
Sign up to set email alerts
|

Learning from Experiment: Unio Freshwater Mussel Shells in Fifth-millennium bc Romania

Abstract: Raw materials from aquatic environments were systematically used for domestic activities even before the appearance of modern humans. Here, the authors analyse the possible use of freshwater mussel valves of the Unio species, whose surfaces preserve marks resulting from their use. They consider the ways in which wear develops on these valves, starting from the comparison between archaeological exemplars and experimental pieces. An experimental programme was developed to record variables such as the procurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Due to the increased fragmentarity, 54 valves were classified only at the genus level (Unio sp.). Experimental studies have shown that valves with wear traces could be used to process ceramics [37]. On eight of these valves, it was possible to identify spots of red pigments (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the increased fragmentarity, 54 valves were classified only at the genus level (Unio sp.). Experimental studies have shown that valves with wear traces could be used to process ceramics [37]. On eight of these valves, it was possible to identify spots of red pigments (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Usually, they fed on detritus and phytobenthic species (Makhutova et al, 2013), and for this reason, naiads qualify as a convenient isotopic baseline for comparisons of pelagic food webs (McKinney et al, 1999;Vuorio et al, 2007). (Radu, 2011;Radu et al, 2016) and as raw material for producing tools or ornaments (Mărgărit et al, 2018(Mărgărit et al, , 2021.…”
Section: Naiads Ecologymentioning
confidence: 99%
“…During prehistory, molluscs were exploited opportunistically in relationship with the surrounding environment: as an essential source of food (Radu, 2011;Radu et al, 2016) and as raw material for producing tools or ornaments (Mărgărit et al, 2018(Mărgărit et al, , 2021.…”
Section: Archaeological Datamentioning
confidence: 99%